STUDY OF SOME FRUITS CHARACTERS OF LEMON Citrus limon VARIETIES AND SOME RELATIONSHIPE HYBRID CULTIVATED IN IRAQ - AL- Hamdani, Khalid A.; Hussein, Fireawn A.; Ehraib, Siham A. (Diyala Agricultural Sciences Journal, 2013)
This study was conducted in private orchard in Doura region- Baghdad through the agricultural season 2011 and 2012 on certain lemon varieties. The aim of study to know the physical and chemical fruit Characters .The study showed superiority of Panda rosa var. in physical changes (fruit weigh, fruit juice weight, fruit skin thickness , seed number) successively, the Mahali variety had less fruit weight juice fruit weight (80.20 , 31.30 )gm in addition to less fruit skin thickness (0.21 cm) et less seeds number 4.18 seeds/ fruit. The chemical properties (T.S.S, acidity, vitamin C content ,these were significant differences, Mahali variety gave highest percentage of T.S.S 9.75%, but Panda rosa var. less percentage 8.08%. Lisbon variety gave supper percentage of acidity 6.16%, while Mahali var. gave less acidity percentage 0.08%.For the fruit content of vitamin C it was found that Eureka had superior content significantly 51.30 mg/100 gm juice, while Lemon sour(2) had less content 23 mg/100 gm juice.